2019
DOI: 10.5902/1980509831387
|View full text |Cite
|
Sign up to set email alerts
|

Disponibilidade hídrica e fertilização mineral nas características da madeira e do carvão vegetal de <i>Eucalyptus grandis</i> W. Hill ex Maiden

Abstract: As alterações na qualidade da madeira das árvores de Eucalyptus causadas pela fertilização e disponibilidade hídrica podem influenciar as características da biomassa e do carvão vegetal. O objetivo deste trabalho foi avaliar as características da madeira e do carvão vegetal de Eucalyptus grandis sob o efeito da fertilização com potássio e sódio (controle; 4,5 kmol ha-1 de KCl e 4,5 kmol ha-1 de NaCl) e disponibilidade hídrica (100% e 63% das chuvas, com exclusão artificial por lonas em polietileno). Árvores de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…(0.90 g cm -3 ) for 12, both slightly below the maximum obtained by this study, showing that it is a denser wood, perhaps because it suffers the effects of water stress in the Cerrado region where it is planted. SILVA et al (2019), studying mineral fertilization and wood characteristics, observed an increase in wood density in the block with partial exclusion of rainwater in the forest plantation. However, some studies report that trees planted in places with greater availability of water, compared to those of the seed provenance, present vessels with features of a environment et al, 2011a,b;LONGUI et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…(0.90 g cm -3 ) for 12, both slightly below the maximum obtained by this study, showing that it is a denser wood, perhaps because it suffers the effects of water stress in the Cerrado region where it is planted. SILVA et al (2019), studying mineral fertilization and wood characteristics, observed an increase in wood density in the block with partial exclusion of rainwater in the forest plantation. However, some studies report that trees planted in places with greater availability of water, compared to those of the seed provenance, present vessels with features of a environment et al, 2011a,b;LONGUI et al, 2011).…”
Section: Resultsmentioning
confidence: 99%